Strategi Media Relations Humas Kementerian Sosial Republik Indonesia Pada Program Prioritas - Dian Lestari; Menati Fajar Rizki (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2019)
The Ministry of Social Affairs of the Republic of Indonesia is a Government Agency Based on Presidential Regulation No. 46 of 2015 concerning the Ministry of Social Affairs, has the task of organizing affairs in the fields of social rehabilitation, social security, social empowerment, social protection, and handling of the poor. Media relations are conducted regularly but many news are not reported, such as news about the success of the Priority Program, namely Non-Cash Food Assistance (BPNT) and the Family Hope Program (PKH). The purpose of this study is to find out how the social ministry's media relations strategy is to increase publicity in the mass media. Media relations is part of external public relations that fosters and develops good relations with the mass media as a means of communication. Researchers use Frank Jefkins' theory of general principles to foster good media relations or media relations. This research uses descriptive qualitative research, data obtained through primary and secondary data collection. While the research subjects consisted of 1 key informant and 3 informants. Based on the results of research the Ministry of Social Affairs has applied the theory of Frank Jefkins the general principle of fostering good relations, but in the strategy carried out there are still many shortcomings and need to be improved again. From the 6 theoretical points according to Jefkins, by serving the media, by establishing a reputation for reliability, by supplying good copy, by providing cooperation in providing material, by providing verification facilities, by building personal relationships with the media, the Ministry of Social Affairs needs to strengthen media relations in section by providing verifivation facilities, and by building personal relationships with the media. So that the media can report information related to the Indonesian Ministry of Social Affairs and the programs that it runs.